(untitled) (Academicia Globe: Inderscience Research, 2023)
Mathematical modeling provides an opportunity to solve many problematic situations and issues in the field of human life and activity. From this point of view, it is important to pay attention to its initial concepts, main stages and requirements when studying mathematical modeling.